Quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolysis cell
The quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolytic cell addresses inefficiencies in anode replacement and current distribution by using built-in carbon fibers and conductors, improving electrolytic aluminum production efficiency and stability.
Patent Information
- Application Number
- CN202411484819.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-13
AI Technical Summary
Existing electrolytic aluminum production technologies face challenges with high anode replacement frequency, uneven current distribution, and insufficient strength of large anodes, leading to inefficiencies and quality issues in continuous production.
A quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolytic cell design incorporating built-in carbon fibers and conductors to enhance anode strength and improve current distribution, reducing anode replacement frequency and enhancing production efficiency.
The solution improves anode stability and current distribution, reducing anode replacement frequency and increasing the efficiency of electrolytic aluminum production by enhancing the tensile strength and conductivity of large anodes.
Smart Images

Figure CN119121327A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolytic cell, belonging to the technical field of molten salt aluminum electrolytic metallurgy production. Background Art
[0002] The electrolytic cells for molten salt electrolysis aluminum smelting have gone through the stages of small pre-baked anodes, side-inserted self-baked anodes, top-inserted self-baked anodes, and pre-baked anodes according to the characteristics of the anodes. The early electrolytic cells had high power consumption and low current efficiency. With the continuous advancement of technology, the structure of the electrolytic cells has been gradually optimized, and the power consumption and current efficiency have been significantly improved.
[0003] Traditional self-baking cells use plug-in nail rod electrodes, the operating current distribution is uneven, the anode operation is complicated, and it is difficult to achieve automation and intelligence; the workshop air fluoride concentration is high and the environment is harsh; the current efficiency is mostly 88%-90%, and the DC power consumption per ton of aluminum is about 14900kWh, which is high in energy consumption; the cell type is mostly at the 60-90kA level, and it is difficult to further scale up. Although pre-baked cell technology has made great progress in large-scale and automation, the pre-baked anode must go through the process steps of sintering large long carbon blocks-cutting-anode steel claw casting, and there are still obvious shortcomings such as long process and interference of the stability of the electrolytic cell during the pole changing process. For inert anodes, it means that the anode will not be consumed by oxidation, and is usually made of alloy or metal ceramics. Inert anodes were previously designed in sheet form. However, it is found in practice that many inert anode materials are not completely immune to oxidation, but have a slower oxidation corrosion rate and will gradually be consumed. After a long time, the inert anode must be replaced. Therefore, this patent proposes a design concept of quasi-continuous inert anode, while still using traditional pre-baked block anodes. The problem is that it is difficult to ensure the uniformity of the inert anode sintering, and it cannot maintain strength in a high-temperature, strong oxidizing environment.
[0004] In summary, the existing technology cannot realize continuous electrolytic aluminum production process due to the high frequency of anode replacement, uneven anode current distribution, and insufficient strength of large anodes, which further affects the efficiency and quality of electrolytic aluminum production. Summary of the invention
[0005] In view of the current problems of high frequency of anode replacement, uneven anode current distribution and insufficient strength of large anodes, which lead to the inability to continuously produce electrolytic aluminum, the present invention proposes a quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolytic cell, which uses built-in carbon fiber to enhance the strength of large anodes, and uses built-in conductors and carbon fiber conductors to solve the problems of high carbon block resistance and uneven current distribution, ultimately reducing the frequency of anode replacement and improving the efficiency of electrolytic aluminum production.
[0006] The technical solution adopted by the present invention to solve the technical problem is:
[0007] A quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolytic cell, comprising an electrolytic cell, the inner wall of which is fitted with a cathode lining 13, the bottom of which is provided with a cathode carbon block 12 fitted with the cathode lining 13, and the electrolytic cell is filled with a molten salt electrolyte;
[0008] An anode structure is provided in the electrolytic cell, and the anode structure includes a prebaked inert or carbon block anode 8, a plurality of vertical carbon fibers 5 are evenly arranged inside the prebaked inert or carbon block anode 8, an anode busbar is arranged at the top of the carbon fiber 5, a vertical central threaded hole is opened in the center of the prebaked inert or carbon block anode 8, an anode metal guide rod 4 is inserted into the central threaded hole, and a guide rod anode busbar 3 is arranged at the top of the anode metal guide rod 4; the anode metal guide rod 4 is built-in in the center of the prebaked inert or carbon block anode 8, which saves the operation of pulling out and inserting nail rods, improves the sealing effect of the electrolytic cell, reduces the frequency of replacing the anode, and improves the efficiency of electrolytic aluminum production.
[0009] A steel beam 1 is fixedly installed directly above the electrolytic cell, and a first hanger 2 and a second hanger 6 are vertically installed on the steel beam 1. The bottom end of the first hanger 2 is fixedly connected to the top center of the anode metal guide rod 4. The second hanger 6 is located on both sides of the prebaked inert or carbon block anode 8. The second hanger 6 is fixedly connected to the prebaked inert or carbon block anode 8 through a plurality of anode clamps 7.
[0010] The anode clamp 7 is an open frame structure matching the prebaked inert or carbon block anode 8, the open frame structure is sleeved on the prebaked inert or carbon block anode 8, a first fastening bolt is arranged at the opening of the anode clamp 7, and fixing protrusions are arranged on opposite sides of the anode clamp 7, and the fixing protrusions are fixedly connected to the second hanger 6 through second fastening bolts.
[0011] Preferably, the anode metal guide rod 4 is provided with an external thread, and the anode metal guide rod 4 is connected to the prebaked inert or carbon block anode 8 via the external thread.
[0012] The preparation method of the anode structure comprises the following specific steps:
[0013] 1) placing an inert composite powder or a carbon block or carbon fiber into a molding machine, presetting a vertical central threaded hole, and pressing under high pressure to form a preliminary anode blank, wherein the inert composite powder includes SnO2, NiFe2O4, NiO, Fe2O3, Cu2O, WC, Ni, Fe, Co or Cr powder;
[0014] 2) The preliminary anode blank is preheated and then sintered in a low oxygen environment to form a prebaked inert or carbon block anode.
[0015] Beneficial effects of the present invention:
[0016] The present invention adopts built-in carbon fiber to enhance the strength of large anodes, and adopts built-in conductors and carbon fiber conductors to solve the problems of short replacement cycle of aluminum electrolytic anodes, low tensile strength of carbon blocks, high resistance and uneven current distribution, ultimately reducing the replacement frequency of anodes and improving the efficiency of electrolytic aluminum production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the structure of a quasi-continuous large-scale pre-baked inert or carbon block anode aluminum electrolysis cell;
[0018] Figure 2 It is a top view schematic diagram of the anode clamp; in the figure, 1-steel beam, 2-first hanger, 3-guide rod anode busbar, 4-anode metal guide rod, 5-carbon fiber, 6-second hanger, 7-anode clamp, 8-prebaked inert or carbon block anode, 9-alumina, 10-molten salt electrolyte, 11-aluminum liquid, 12-cathode carbon block, 13-cathode lining. DETAILED DESCRIPTION
[0019] The present invention provides a quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolytic cell, which solves the problem that the existing technology cannot continuously produce electrolytic aluminum due to the high replacement frequency of anodes and uneven current distribution of carbon blocks. The present invention adopts large anodes, combined with built-in anode conductors and conductive carbon fiber structures, increases the tensile strength of the anodes, reduces the replacement frequency of the anodes, and improves the efficiency of electrolytic aluminum production.
[0020] Below, the technical solutions in the present invention will be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments of the present invention. It should be understood that the present invention is not limited to the example embodiments described herein. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should also be noted that, for the convenience of description, only the parts related to the present invention are shown in the accompanying drawings, rather than all of them.
[0021] like Figure 1 As shown, a quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolytic cell comprises an electrolytic cell, the inner wall of the electrolytic cell is fitted with a cathode lining 13, the bottom of the electrolytic cell is provided with a cathode carbon block 12 fitted with the cathode lining 13, and the electrolytic cell is filled with a molten salt electrolyte 10; the electrolytic cell is provided with a liquid inlet and an exhaust port, the molten salt electrolyte 10 is filled through the liquid inlet, the raw material aluminum oxide 9 to be electrolyzed is added to the molten salt electrolyte 10, the aluminum liquid 11 produced by electrolysis is deposited at the bottom of the electrolytic cell, and the gas produced during the electrolysis process is discharged through the exhaust port;
[0022] The cathode carbon block 12 can be made of high-quality anthracite, coke, graphite and other materials, and is prepared through calcination, crushing, screening, kneading, molding and sintering processes. It has good electrical conductivity and can resist the erosion of high-temperature molten salt electrolyte 10 and aluminum liquid 11, protecting the electrolytic cell from damage; the cathode lining 13 has good sealing performance and can resist the erosion of high-temperature molten salt electrolyte 10 and aluminum liquid 11, protecting the electrolytic cell shell from damage, and extending the service life of the electrolytic cell;
[0023] The electrolytic cell is provided with an anode structure, which includes a prebaked inert or carbon block anode 8, a plurality of vertical carbon fibers 5 are evenly arranged in the middle of the prebaked inert or carbon block anode 8, the top of the carbon fiber 5 extends to the outside of the prebaked inert or carbon block anode 8, and an anode busbar is arranged at the top of the carbon fiber 5; a vertical central threaded hole is opened in the center of the prebaked inert or carbon block anode 8, an anode metal guide rod 4 is inserted in the central threaded hole, a guide rod anode busbar 3 is arranged at the top of the anode metal guide rod 4, and the guide rod anode busbar 3 and the anode busbar are both externally connected to the positive pole of the power supply; specifically, an external thread is arranged on the anode metal guide rod 4, and the anode metal guide rod 4 is connected to the prebaked inert or carbon block anode 8 through the external thread; the anode metal guide rod 4 is built-in in the center of the prebaked inert or carbon block anode 8, which saves the operation of pulling out and inserting nail rods, reduces the frequency of anode replacement, and improves the efficiency of electrolytic aluminum production;
[0024] The anode structure is the part connected to the positive electrode of the power supply during the electrolysis process, responsible for conducting current and participating in the electrochemical reaction; the prebaked inert or carbon block anode 8 is one of the key components in the aluminum electrolytic cell, not only as a medium for current conduction, but also as an important part participating in the electrolysis reaction; during the electrolysis process, the prebaked inert or carbon block anode 8 will be gradually consumed; the prebaked inert or carbon block anode 8 has high conductivity and corrosion resistance;
[0025] The carbon fiber 5 in the anode structure penetrates the prebaked inert or carbon block anode 8 to ensure that the current can pass through the prebaked inert or carbon block anode 8 evenly and smoothly; the anode busbar and the guide rod anode busbar 3 can both be made of highly conductive copper wires, and their design and layout need to take into account the uniformity of current distribution and the overall stability of the electrolytic cell;
[0026] The anode metal guide rod 4 can further ensure the stable transmission of current. The presence of the anode metal guide rod 4 and the carbon fiber 5 enhances the overall stability of the anode structure and helps to optimize the current distribution.
[0027] A steel beam 1 for hoisting the anode metal guide rod 4 and the prebaked inert or carbon block anode 8 is fixedly arranged directly above the electrolytic cell, and a first hanger 2 and a second hanger 6 are vertically arranged on the steel beam 1, wherein the first hanger 2 is located in the middle of the steel beam 1, and the bottom end of the first hanger 2 is fixedly connected to the top center of the anode metal guide rod 4, and the second hanger 6 is located on both sides of the prebaked inert or carbon block anode 8, and the second hanger 6 is fixedly connected to the prebaked inert or carbon block anode 8 through a plurality of anode clamps 7; the anode clamps 7 are evenly distributed on the second hanger 6, and are used to bear part of the weight of the prebaked inert or carbon block anode 8 in sections; the steel beam 1 meets the load-bearing requirements of the prebaked inert or carbon block anode 8, ensuring that it will not break or deform during the hoisting process.
[0028] The first hanger 2, the second hanger 6, and the anode clamp 7 form a fixing device, which can ensure that the anode structure remains stable during the electrolysis process. The anode clamp 7 is preferably a frame fastening structure, which is used to fix the prebaked inert or carbon block anode 8 in sections and bear the anode weight in sections. Since the prebaked inert or carbon block anode 8 and the anode metal guide rod 4 are subjected to greater stress during the electrolysis process, the anode clamp 7 needs to have higher strength to withstand these stresses. During the electrolysis process, as the prebaked inert or carbon block anode 8 is consumed and becomes shorter, the first hanger 2 and the second hanger 6 are gradually lowered.
[0029] The anode clamp 7 is preferably made of corrosion-resistant material to adapt to the harsh environment in the electrolytic cell and extend its service life.
[0030] When the prebaked inert or carbon block anode 8 is a carbon anode, the raw materials mainly include aggregates such as petroleum coke and asphalt coke, and binders such as coal tar pitch; when the prebaked inert or carbon block anode 8 is a prebaked inert anode, the raw materials mainly include SnO2, NiFe2O4, NiO, Fe2O3, Cu2O, WC, Ni, Fe, Co or Cr powder, which undergoes pretreatment processes such as calcination, crushing, and screening to achieve the particle size and purity requirements required for molding.
[0031] The carbon fiber is in the form of fiber, fiber tape, fiber rope or fiber cloth;
[0032] A plurality of supporting cross bars are fixedly arranged on the prebaked inert or carbon block anode 8, and the ends of the supporting cross bars are fixedly connected to the second hanger 6 through the anode clamp 7; the supporting cross bars can greatly increase the structural stability of the prebaked inert or carbon block anode 8, and strengthen the fixing stability of the prebaked inert or carbon block anode 8 and the second hanger 6.
[0033] The method for preparing the anode structure of the present invention comprises the following specific steps:
[0034] 1) Fixing carbon fiber in a mold, filling the mold with a paste of inert composite powder or carbon block, and then putting it into a molding machine for vibration molding and high-pressure pressing to form a preliminary anode blank with a certain strength and density, and then presetting a vertical center threaded hole by mechanical drilling, laser drilling or chemical corrosion; the inert composite powder includes SnO2, NiFe2O4, NiO, Fe2O3, Cu2O, WC, Ni, Fe, Co or Cr powder; vibration during high-pressure pressing helps to reduce the friction between the materials, so that the materials are rearranged in the mold and more tightly combined;
[0035] 2) The preliminary anode blank is preheated in a low-temperature preheating furnace to remove moisture and volatiles in the preliminary anode blank, reduce stress and cracking caused by rapid temperature rise during sintering, and improve sintering efficiency. Then, in an oxygen-free environment (nitrogen, inert gas or vacuum), high-temperature sintering is performed at a temperature of 1200-1800°C to cause physical and chemical changes in the anode green body (preliminary anode blank), thereby improving its mechanical strength, chemical stability and electrical conductivity, forming a prebaked inert or carbon block anode, and combining carbon fiber with an inert anode matrix (SnO2, NiFe2O4, NiO, Fe2O3, Cu2O, WC, Ni, Fe, Co or Cr) to form a composite structure, or combining carbon fiber with a carbon matrix (petroleum coke, asphalt coke, etc.) to form a composite structure; after roasting, the anode metal guide rod 4 is screwed into the central threaded hole, and the extended carbon fiber is arranged into a bundle.
[0036] During the high-temperature sintering process, the pores in the preliminary anode blank will gradually disappear or decrease, and the preset carbon fiber 5 will be tightly combined with the main material of the preliminary anode blank (the metal and metal ceramic of the inert anode matrix, or the carbon particles of the carbon matrix to form a carbon fiber reinforcement phase, thereby improving the tensile strength of the anode, reducing the anode resistance, and promoting the electrolysis reaction).
[0037] The height of the prebaked inert or carbon block anode 8 is 300-500 mm, which is a block anode. In the process of continuous production of aluminum in the electrolytic cell, only 5 sides of the block anode are immersed in the electrolyte, allowing the anode to be gradually consumed, and then the upper anode gradually descends to ensure the inter-electrode spacing. The prebaked anode with a height of 300-500 mm has the characteristics of more stable current, higher current density and longer service life.
[0038] The central threaded hole preset in the center of the prebaked inert or carbon block anode 8 can realize a detachable connection between the prebaked inert or carbon block anode 8 and the anode metal guide rod. The threaded connection can provide a relatively stable connection effect, ensuring that the anode metal guide rod 4 is not easy to loosen or fall off during the electrolysis process; due to the threaded connection, the anode metal guide rod 4 and the prebaked inert or carbon block anode 8 can be easily screwed in and out, which is convenient for the descent and ascent of the prebaked inert or carbon block anode 8, and ensures that the anode metal guide rod 4 does not touch the electrolyte.
[0039] The anode clamp 7 is an adjustable frame fastening structure (see Figure 2 ), the open frame structure is sleeved on the prebaked inert or carbon block anode 8, a first fastening bolt is arranged at the opening of the anode clamp 7, and fixing protrusions are arranged on opposite sides of the anode clamp 7, and the fixing protrusions are fixedly connected to the second hanger 6 through the second fastening bolts; specifically, the anode clamp 7 is adjusted to a tightness by the first fastening bolt to adjust the anode clamp 7 to hold the prebaked inert or carbon block anode 8 tightly, to ensure that it can share part of the weight of the prebaked inert or carbon block anode 8, and to reduce the tensile stress on the upper part of the prebaked inert or carbon block anode 8.
[0040] The specific embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolysis cell, characterized in that: The electrolytic cell comprises an electrolytic cell, wherein a cathode lining (13) is provided on the inner wall of the electrolytic cell, a cathode carbon block (12) which is provided on the bottom of the electrolytic cell and is in contact with the cathode lining (13), and the electrolytic cell is filled with a molten salt electrolyte; The electrolytic cell is provided with an anode structure, the anode structure comprising a prebaked inert or carbon block anode (8), a plurality of vertical carbon fibers (5) are evenly arranged inside the prebaked inert or carbon block anode (8), an anode busbar is arranged at the top of the carbon fiber (5), a vertical central threaded hole is opened at the center of the prebaked inert or carbon block anode (8), an anode metal guide rod (4) is inserted into the central threaded hole, and a guide rod anode busbar (3) is arranged at the top of the anode metal guide rod (4); A steel beam (1) is fixedly arranged directly above the electrolytic cell, and a first hanger (2) and a second hanger (6) are vertically arranged on the steel beam (1). The bottom end of the first hanger (2) is fixedly connected to the top center of the anode metal guide rod (4), and the second hanger (6) is located on both sides of the prebaked inert or carbon block anode (8). The second hanger (6) is fixedly connected to the prebaked inert or carbon block anode (8) through a plurality of anode clamps (7).
2. The quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolysis cell according to claim 1, characterized in that: The anode clamp (7) is an open frame structure matching the prebaked inert or carbon block anode (8), the open frame structure is sleeved on the prebaked inert or carbon block anode (8), a first fastening bolt is arranged at the opening of the anode clamp (7), and fixing protrusions are arranged on opposite sides of the anode clamp (7), and the fixing protrusions are fixedly connected to the second hanger (6) through second fastening bolts.
3. The quasi-continuous large-scale prebaked inert or carbon block anode aluminum electrolysis cell according to claim 1, characterized in that: The preparation method of the anode structure comprises the following specific steps: 1) placing an inert composite powder or a carbon block or carbon fiber into a molding machine, presetting a vertical central threaded hole, and pressing under high pressure to form a preliminary anode blank, wherein the inert composite powder includes SnO2, NiFe2O4, NiO, Fe2O3, Cu2O, WC, Ni, Fe, Co or Cr powder; 2) The preliminary anode blank is preheated and then sintered in an oxygen-free environment to form a prebaked inert or carbon block anode.
